Learners’ Profile Across Programs and Research Writing Background - Castro, Rein Mark F. (Future Science / FSH-PH Publications, 2025)
his study utilized a descriptive-correlational research design to inves-tigate the relationship between learners' profile and their research writing background among 276 students at Osias Colleges Incorpo-rated. The instrument underwent pilot testing, achieving a Cronbach's alpha value of 0.94, indicating high reliability. Data analy-sis involved statistical methods including frequency counts, percent-ages, means, and chi-square tests to interpret the findings accurately.The results revealed that most participants were male freshmen aspiring to become criminologists. In terms of their research writing background, learners demonstrated a solid understanding of the re-search writing process, reported significant experience, and ex-pressed confidence in their writing abilities. Notably, the study found that both gender and year level significantly influenced students' awareness, experience, and competence in research activities, sug-gesting that as students advance academically, their engagement with research writing improves. However, the specific courses taken did not appear to significantly impact on students' experiences or compe-tencies, indicating a need for curricular enhancements across disci-plines. To address these findings, the study proposed an action plan aimed at improving learners' research writing engagements. This includes implementing a mentorship program that pairs students with experienced faculty or upperclassmen to provide guidance on academic challenges and research skills. Additionally, interactive workshops focused on advanced research writing techniques should be organized to facilitate hands-on learning experiences. Establishing a curriculum review committee (with representatives from various programs) would help assess how effectively different courses pro-mote research skills and identify best practices for enhancing student engagement in research activities across all programs.